Evaluation of the Incidence of Psychiatric Disorders in Dialysis Patients: Cross-Sectional Study - Farjamfar 1, Maryan; Binesh 1, Ehsan; Moazamian 1, Dina; Mousavi 2, Sina; Nasiri 1*, Mojtaba (Shahroud Journal of Medical Sciences, 2017)
Background: Psychiatric problems are an important concern in chronic illness such as chronic kidney disease. Knowing the frequency of psychiatric disorders may be helpful for improving quality of life in dialysis patients. This study was performed to evaluate psychiatric disorders in patients with chronic renal failure under treatment with dialysis from February 2013 to February 2014 in Shahroud, Iran.Methods: In this cross-sectional descriptive comparative study, 98 dialysis patients were enrolled and psychiatric disorders were determined by SCL-90-R questionnaire.Results: The results demonstrated that 33 patients (33.7%) had psychiatric disorders, of which 18 patients had major depressive disorder, six had anxiety disorders, six had psychotic disorders and one case having paranoid thoughts, one patient had obsessive compulsive disorder (OCD), and one patient had phobia disorder.Conclusions: Totally, according to the obtained results in this study it may be concluded that nearly one-third of dialysis patients have psychiatric disorders, with most of these being major depressive disorder.